Investigating Satirical Interpretation of Netizen Comments on Tiktok Toward Megawati - Era Mita Theresia Simamora; Arsen Nahum Pasaribu; Jubil Ezer Sihite (Journal of Language Education (JoLE), 2025)
Freely to express opinions is one of the reasons netizens use social media as a forum for expressing themselves. Through the comments column, netizens on TikTok use elements of satirical language to criticize, satirize Megawati with a sense of humor using polite and even vulgar language. The aim of this research is to discuss the satirical interpretation of people's comments on TikTok towards Megawati. The data was taken from 50 netizen comments on the official TikTok account Inilah.com. The results of this study show that there are three types of satire used by netizens to criticize Megawati, namely Horatian Satire, Juvenalian Satire and Manippean Satire, and netizens use Horatian satire as the dominant type with a percentage of 58% of all data analysis. In clarifying the data, the writer use descriptive qualitative research with analytical description method. The data were analyzed using Harmon and Holman's theory. For practical purposes, it is hoped that the results of this research can become a new model for the study of satire. Theoretically, satire is not only used on social media but also elsewhere as a way for people to express their opinion about a subject and show that people are wiser in using their language for a particular purpose.